Trends and practices in English language assessment in ASEAN countries: A meta-synthesis study (2021-2025) - Bacus, Remedios; Trasmil, Reynarose (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Across the linguistically diverse ASEAN (Association of Southeast Asian Nations) member states, English has been acknowledged as the sole official working language. It serves as a unifying medium in business, diplomacy, and education. This study explores emerging assessment practices and methodologies in English language teaching within the regional context over the last five years, considering Kachru’s 3 Concentric Circles Model of the English Language.  Using databases and following the PRISMA flow, the selected articles were verified by the three experts in English language teaching.  A total of 12 published articles met the eligibility criteria: four from Malaysia, four from the Philippines, and four from Indonesia. With Braun and Clarke’s thematic analysis steps, key factors influencing English language assessment were identified from the validated studies: benchmarking, learner autonomy, ICT integration, upskilling, and preparation for workforce demand. Based on these insights, the meth-synthesis proposes a new framework aimed at addressing the identified challenges.  The findings of this study have significant implications for enhancing the quality of English language assessment across ASEAN countries.